Solar Thermochemical Fuel Production: A Novel, Validated Multiphysics Reactor Model for the Reduction–Oxidation of Nonstoichiometric Redox Cycles - Francesco Orsini; Domenico Ferrero; Davide Papurello; Massimo Santarelli (Energies)
Apparent kinetics is often used to describe a variety of reactions in the field of chemical looping and solar thermochemical processes, yet a rigorous analytical methodology for utilizing such kinetics has been lacking. The implementation of a novel approach was exemplified in the ceria thermochemical cycle for producing solar thermochemical hydrogen, specifically in the H2O-driven oxidation step. The H2 production rate equation was derived, rearranging apparent kinetics from experimental data in the literature into a more suitable analytical form. The 1D model integrates heat transfer, fluid dynamics, and redox chemistry, providing the description of a directly irradiated solar receiver–reactor. Model robustness is ensured through the oxygen mass balance across the cycle, and the comparison against experimental data shows high agreement. The methodology can be useful for simulating chemical looping cycles using any nonstoichiometric oxide, such as ceria-based oxides and, most importantly, oxidation-limited perovskites, for which optimizing the oxidation step in terms of fluid flow, kinetics, and reaction times is crucial. The proposed analytical model can be applied to arbitrarily complex reactor geometries. The inherently local nature of the model also allows the spatial distributions of the redox material’s conversion and utilization to be obtained, paving the way for optimization strategies of the reactor’s design and operation.